2000
DOI: 10.1006/jmre.1999.1953
|View full text |Cite
|
Sign up to set email alerts
|

Toroid Cavity Detectors for High-Resolution NMR Spectroscopy and Rotating Frame Imaging: Capabilities and Limitations

Abstract: The capabilities of toroid cavity detectors for simultaneous rotating frame imaging and NMR spectroscopy have been investigated by means of experiments and computer simulations. The following problems are described: (a) magnetic field inhomogeneity and subsequent loss of chemical shift resolution resulting from bulk magnetic susceptibility effects, (b) image distortions resulting from off-resonance excitation and saturation effects, and (c) distortion of lineshapes and images resulting from radiation damping. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The B 1 field for a toroidal geometry varies inversely with radial distance r as detailed more fully in [17,29,30]. Hence, the corresponding rf amplitude, m rf (r) = cB 1 (r)/(2p), can be expressed relative to its smallest value at r max as m rf (r) / m rf (r max )/r to obtain…”
Section: Toroid Probesmentioning
confidence: 99%
“…The B 1 field for a toroidal geometry varies inversely with radial distance r as detailed more fully in [17,29,30]. Hence, the corresponding rf amplitude, m rf (r) = cB 1 (r)/(2p), can be expressed relative to its smallest value at r max as m rf (r) / m rf (r max )/r to obtain…”
Section: Toroid Probesmentioning
confidence: 99%
“…Among many other successful examples of palladium chemistry in ILs are the Stille coupling [71] and a copper-free version of the Sonogashira coupling [72] which has additionally been applied to a microflow system for efficient catalyst recycling. Revell and Ganesan [73] have demonstrated that the rate-accelerating IL effects can also be transferred to solid-phase conditions.…”
Section: Palladium-catalysed C -C-coupling Reactionsmentioning
confidence: 99%
“…However, this method requires that T Ã 2 be longer than at least n times the probe dead time, where n is the number of pulses applied. Another, more important problem in nutation experiments for samples with T 1 ) T Ã 2 is appearance of ''nonlinear but periodic distortions'' [5] caused by incomplete relaxation. Therefore, for samples with T Ã 2 lifetimes shorter than hundreds of microseconds, this method is hard to implement.…”
Section: Introductionmentioning
confidence: 99%